2018
DOI: 10.1038/s41598-018-23695-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of induced abortion with preterm birth risk in first-time mothers

Abstract: Women who have previously had an induced abortion (IA) before their first birth have been associated with preterm birth (PTB). However, previous studies on the PTB are inconsistent. Therefore, the aim of this study was to clarify the association between IA and PTB and low birth weight (LBW) for first-time mothers. A total of 3,684 Southern Chinese women who gave birth for the first time to a live singleton infants were recruited between January 2015 and December 2015 in the province of Guangdong, China. Univar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
2
12
0
2
Order By: Relevance
“… 31 41 The findings of this study indicate there is a higher likelihood for women who had ever had a pregnancy terminated of giving birth to LBW babies that resonates with other research projects. 27 42 However, contrary to these findings, Ke et al 43 observed no significant association between induced abortion and LBW for first-time mothers among southern Chinese women. This study’s findings of the high likelihood of women giving birth to LBW babies that had experienced any form of IPV, either physical or sexual, is supported by earlier study results.…”
Section: Discussionmentioning
confidence: 88%
“… 31 41 The findings of this study indicate there is a higher likelihood for women who had ever had a pregnancy terminated of giving birth to LBW babies that resonates with other research projects. 27 42 However, contrary to these findings, Ke et al 43 observed no significant association between induced abortion and LBW for first-time mothers among southern Chinese women. This study’s findings of the high likelihood of women giving birth to LBW babies that had experienced any form of IPV, either physical or sexual, is supported by earlier study results.…”
Section: Discussionmentioning
confidence: 88%
“…Hence stress-depression is associated with previous abortion [23] and other pregnancy complications [24] and lowers dietary diversity of women [25,26], reduces fetal nutrients vital for development leads to an increased risk of LBW [27][28][29][30]. Conversely, various kinds of literature suggested that induced abortion does not increase the risk for low birth weight in the subsequent pregnancy [31][32][33]. This might be explained by the differences in the methods used to perform abortion at different times and different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Jena et al (6) reported that there is a dynamic balance of macrophage polarization patterns in the endometrium in response to the menstrual cycle, suggesting that this model is appropriate for assessing endometrial receptivity in patients with IVF failure due to WOI changes. Importantly, uterine cavity procedures (induced abortion, adhesiolysis, or polypectomy), in ammatory responses and transient immune dysregulation (dysbacteriosis or endometritis) due to stress can lead to embryonic implantation failure (35,36).…”
Section: Discussionmentioning
confidence: 99%